The impact analysis characteristics of a ship's bow during collisions. (June 2019) - AbuBakar, A.; Dow, R.S.
Abstract: The incidence of ship collisions and grounding has made a significant contribution to the oil spill, loss of life and environmental damage at sea. The costs incurred due to these accidental scenarios and the time taken for the polluted environmental area to recover to its original state is significantly large. The study employed the effect of rupture due to excessive plasticity which leads to material failure. The study investigates the effect of collision angle and ships speed, when looking at an extreme collision event of a ship striking a rigid wall, a full ship model is employed in this investigation. The study also introduced a rigidity ratio for the forward part of the ship structure as a new parameter for ship collision damage prediction. The numerical simulation findings are used as the basis of a new simplified procedure for predicting damage response of the bow structure during collision events, the numerical results are also compared with more simple analytical calculations. The correlation between the numerical simulations and available current analytical approach applied in Eurocode and other empirical approach show good agreement. Abaqus explicit nonlinear finite element method (NFEM), using explicit dynamic integration calculation was used to simulate the ship collision events. Highlights: The study investigates the ship response during collision using a full ship model. The study introduced a rigidity ratio as a new parameter for ship collision damage prediction. The simplified procedure for predicting damage response of the bow structure during collision events is established. The current analytical approach shows good agreement with the available methods presented.